2021
DOI: 10.3390/computers10100132
|View full text |Cite
|
Sign up to set email alerts
|

Gamification as a Strategy to Increase Motivation and Engagement in Higher Education Chemistry Students

Abstract: In the last year, educational experiences have become increasingly challenging due to teaching classes remotely. For this reason, it has been necessary to develop educational strategies that accompany the use of new technologies to maintain student interest. One of these methodologies is gamification, implemented in school environments more frequently due to the pandemic and whose impact on student motivation and engagement needs to be explored. The literature shows that student participation in these contexts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 40 publications
9
49
1
3
Order By: Relevance
“…Within educational contexts, gamification promotes friendly competition, rewards effort, motivates and engages students using game elements, which they are already familiar with [7]. Therefore, gamification has already been implemented and evaluated within several educational subjects, such as science, technology, engineering, art and mathematics (STEAM) [106,107], language learning [108,109], medical and healthcare education [110][111][112], anatomy [113], sports and physical education [114,115], geometry [116], chemistry [117,118], physics [119], mathematics [120,121], astronomy [122], geography [123], environmental science [124,125], natural science [126], history and cultural heritage education [127,128], music [129], and vocational education [130].…”
Section: Gamification In Educationmentioning
confidence: 99%
“…Within educational contexts, gamification promotes friendly competition, rewards effort, motivates and engages students using game elements, which they are already familiar with [7]. Therefore, gamification has already been implemented and evaluated within several educational subjects, such as science, technology, engineering, art and mathematics (STEAM) [106,107], language learning [108,109], medical and healthcare education [110][111][112], anatomy [113], sports and physical education [114,115], geometry [116], chemistry [117,118], physics [119], mathematics [120,121], astronomy [122], geography [123], environmental science [124,125], natural science [126], history and cultural heritage education [127,128], music [129], and vocational education [130].…”
Section: Gamification In Educationmentioning
confidence: 99%
“…While the Plickers application can attract the topic of third-year remuneration, as well as the interview findings, prove that students do not feel bored during the learning sessions (Tan & Tasir, 2022). Results from the pre-and post-test findings of the Chans & Castro (2021) research showed assignment scores, ticket acceptance, tokens, and gamification element bonuses led to high achievement in Wordwall games. The interview findings of Ahmed & Asiksoy (2021) clarifies gaming elements through Classical Flipped Learning (CFL) increase motivation as well as support students learning.…”
Section: Research Question 2: Does Gamification Motivate Students In ...mentioning
confidence: 69%
“…The Chans & Castro (2021) research found that the gamification approach encourages extensive student engagement. In addition, students majoring in chemistry found gamification easier to relate to the content of chemistry lessons, and non-chemistry students found gamification more interesting and showed positive interest and attitude in learning.…”
Section: Research Question 3: Does Gamification Affect Students' Perc...mentioning
confidence: 99%
“… 68 In this way, interactive simulations that support multirepresentational fluency are considered critical by the chemistry education community. 69 There are various studies reporting the efforts made to overcome such deficiencies and offering suggestions of teaching approaches to enhance students’ learning (e.g., the blended learning approach, 70 flipped courses, 19 gamification, 71 active learning environment, 72 , 73 virtual lab simulations 69 , 74 ). All of these strategies attempt to engage students in active, constructive, and cooperative learning activities.…”
Section: Discussionmentioning
confidence: 99%